Real-Time PCR Identification of Unique Bacillus anthracis Sequences - Cieślik, P; Knap, J; Kolodziej, M; Mirski, T; Joniec, J; Graniak, G; Zakowska, D; Winnicka, I; Bielawska-Drózd, A (Folia biologica, 2015)
Bacillus anthracis is a spore-forming, Gram-positive microorganism. It is a causative agent of anthrax, a highly infectious disease. It belongs to the "Bacillus cereus group", which contains other closely related species, including Bacillus cereus, Bacillus thuringiensis, Bacillus mycoides, Bacillus weihenstephanensis, and Bacillus pseudomycoides. B. anthracis naturally occurs in soil environments. The BA5345 genetic marker was used for highly specific detection of B. anthracis with TaqMan probes. The detection limit of a real-time PCR assay was estimated at the level of 16.9 copies (CI95% - 37.4 to 37.86, SD = 0.2; SE = 0.118). Oligonucleotides designed for the targeted sequences (within the tested locus) revealed 100 % homology to B. anthracis strain reference sequences deposited in the database (NCBI) and high specificity to all tested B. anthracis strains. Additional in silico analysis of plasmid markers pag and cap genes with B. anthracis strains included in the database was carried out. Our study clearly indicates that the BA5345 marker can be used with success as a chromosomal marker in routine identification of B. anthracis; moreover, detection of plasmid markers indicates virulence of the examined strains.
Keywords: Virulence Factors; antigeny bakteriální; Bacterial Toxins; DNA bakterií; bakteriální proteiny; Bacterial Proteins; DNA, Bacterial; Sensitivity and Specificity; senzitivita a specificita; plazmidy; Antigens, Bacterial; bakteriální toxiny; Bacillus anthracis; Plasmids; genetické markery; Bacillus cereus; kvantitativní polymerázová řetězová reakce; faktory virulence; Real-Time Polymerase Chain Reaction; Genetic Markers